TANTANGAN, PELUANG, DAN IMPLEMENTASI PENDIDIKAN DI ERA DIGITAL - Framesty Basviadha; Muhammad Akmal Fadli; Muhammad Ilham Cholid; Nadhilah; Putri Feby Andhini; Sesilia Triana; Silfi Aminatuzzuhriyah; Sri Qorina; Sukatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has transformed the education sector, affecting both the learning process and the management of educational institutions. This study aims to examine the challenges, opportunities, and implementation of digital technology in education using a qualitative approach through library research based on books, journal articles, and other scholarly references. The findings indicate that digital education continues to face several challenges, including unequal technological infrastructure, limited internet access, the digital divide, curriculum adaptation, and differences in teachers' digital competencies. On the other hand, digital technology expands access to learning resources, supports more flexible and interactive learning, and encourages educational innovation. To maximize these benefits, improvements in infrastructure, digital competencies, and policies that promote equitable access to education are essential. Therefore, collaboration among governments, educational institutions, educators, and communities is crucial to achieving high-quality, equitable, and sustainable education.